Caprine Models of the Agonist-Antagonist Myoneural Interface Implemented at the Above- and Below-Knee Amputation Levels. Issue 2 (August 2019) - Clites, Tyler R.; Carty, Matthew J.; Srinivasan, Shriya S.; Talbot, Simon G.; Brånemark, Rickard; Herr, Hugh M.
Abstract : Background: Traditional approaches to amputation are not capable of reproducing the dynamic muscle relationships that are essential for proprioceptive sensation and joint control. In this study, the authors present two caprine models of the agonist-antagonist myoneural interface (AMI), a surgical approach designed to improve bidirectional neural control of a bionic limb. The key advancement of the AMI is the surgical coaptation of natively innervated agonist-antagonist muscle pairs within the residual limb. Methods: One AMI was surgically created in the hindlimb of each of two African Pygmy goats at the time of primary transtibial amputation. Each animal was also implanted with muscle electrodes and sonomicrometer crystals to enable measurement of muscle activation and muscle state, respectively. Coupled agonist-antagonist excursion in the agonist-antagonist myoneural interface muscles was measured longitudinally for each animal. Fibrosis in the residual limb was evaluated grossly in each animal as part of a planned terminal procedure. Results: Electromyographic and muscle state measurements showed coupled agonist-antagonist motion within the AMI in the presence of both neural activation and artificial muscle stimulation. Gross observation of the residual limb during a planned terminal procedure revealed a thin fibrotic encapsulation of the AMI constructs, which was not sufficient to preclude coupled muscle excursion. Conclusions: These findings highlight the AMI's potential to provide coupled motion of distal agonist-antagonist muscle pairs preserved during below- or above-knee amputation at nearly human scale. Guided by these findings, it is the authors' expectation that further development of the AMI architecture will improve neural control of advanced limb prostheses through incorporation of physiologically relevant muscle-tendon proprioception. Abstract : Supplemental Digital Content is available in the text.